(untitled) (Research, Society and Development, 2018)
In light of the need to consciously use energy resources for sustainable growth, the smart grid concept has served as a reference for the efficient use of such resources, especially the electric. However, the application of such concept in electrical installations requires the development of devices that allow the autonomous monitoring of electrical and electronic appliances in such installations. This article aims to carry out a bibliometric review on non-intrusive load monitoring methods to show the state of the art of this subject, that is, the main advances and obstacles to the development of this technology. A quantitative and qualitative analysis of the works related to the theme searched through the Web of Science database is performed. As result of such research, it is cited the observance of the relevance of the studies in this area, which is in full growth. It is also mentioned the fact that the theme is being investigated in developed countries, like Canada and the United States, as well as in developing countries, like Malaysia and India, which shows that there is a global concern in advancing in such a problem that independent of the nation’s economic situation.